Integration of Targeted Health Interventions into Health Systems : A Conceptual Framework for Analysis - Atun, R.; de Jongh, T.; Secci, F.; Ohiri, K.; Adeyi, O. (2012)
The benefits of integrating programmes that emphasize specific interventions into health systems to improve health outcomes have been widely debated. This debate has been driven by narrow binary considerations of integrated ( horizontal) versus non-integrated ( vertical) programmes, and characterized by polarization of views with protagonists for and against integration arguing the relative merits of each approach. The presence of both integrated and non-integrated programmes in many countries suggests benefits to each approach. While the terms 'vertical' and 'integrated' are widely used, they each describe a range of phenomena. In practice the dichotomy between vertical and horizontal is not rigid and the extent of verticality or integration varies between programmes. However, systematic analysis of the relative merits of integration in various contexts and for different interventions is complicated as there is no commonly accepted definition of 'integration'-a term loosely used to describe a variety of organizational arrangements for a range of programmes in different settings. We present an analytical framework which enables deconstruction of the term integration into multiple facets, each corresponding to a critical health system function. Our conceptual framework builds on theoretical propositions and empirical research in innovation studies, and in particular adoption and diffusion of innovations within health systems, and builds on our own earlier empirical research. It brings together the critical elements that affect adoption, diffusion and assimilation of a health intervention, and in doing so enables systematic and holistic exploration of the extent to which different interventions are integrated in varied settings and the reasons for the variation. The conceptual framework and the analytical approach we propose are intended to facilitate analysis in evaluative and formative studies of-and policies on-integration, for use in systematically comparing and contrasting health interventions in a country or in different settings to generate meaningful evidence to inform policy.